An observational study to assess the clinical profiles of patients with chronic liver disease - Suresh, Anugraha; M. , Praveen (International Journal of Advances in Medicine, 2023)
Background: Chronic liver disease (CLD) is an escalating degradation of the functions of the liver exceeding for more than 6 months with a continued cycle of inflammation, destruction, and regeneration of the liver parenchyma. As per the data obtained from the 2017 Global Burden of Disease, there was a 11.4% increase in CLD related mortality since 2012. Thus, the main objective of this study was to study the clinical profile of patients with CLD. Methods: This was a cross-sectional observational study conducted on 200 patients satisfying the inclusion criteria. The patients with presenting complaints suggesting of CLD were followed for confirmation of diagnosis. History and clinical examination were recorded as per a predefined proforma designed for the study. Results: Almost four-fifth of the participants were male (79.5%). Most of the patients (87.5%) presented with abdominal distension and jaundice (80.5%). Half of the CLD patients (51.5%) belonged to Class B, followed by 46.5% of patients in class C of Child Turcotte Pugh. Liver function test, Renal function test and coagulation profile were deranged in majority of patient and USG abdomen showed features of CLD along with portal hypertension in approximately 82.5% of patients. Conclusions: Male gender in the age-group of 41 to 60 years was mostly affected and mainly belonged to CTP class B and class C. Most common complications observed in CLD patients were hepatic encephalopathy followed by upper gastrointestinal bleed and coagulopathy.